Rationale and Design of the High Platelet Inhibition with Ticagrelor to Improve Left Ventricular Remodeling in Patients with ST-Segment Elevation Myocardial Infarction (HEALING-AMI) Trial - Park, Yongwhi (Korean Circ J, 2019)
BACKGROUND AND OBJECTIVES: Impaired recovery from left ventricular (LV) dysfunction is a major prognostic factor after myocardial infarction (MI). Because P2Y(12) receptor blockade inhibits myocardial injury, ticagrelor with off-target properties may have myocardial protection over clopidogrel. In animal models, ticagrelor vs. clopidogrel protects myocardium against reperfusion injury and improves remodeling after MI. We aimed to investigate the effect of ticagrelor on sequential myocardial remodeling process after MI. METHODS: High platelet inhibition with ticagrelor to improve LV remodeling in patients with ST-segment elevation MI (HEALING-AMI) is an investigator-initiated, randomized, open-label, assessor-blinded, multi-center trial done at 10 sites in Korea. Patients will be enrolled if they have ST-segment elevation MI (STEMI) treated with primary percutaneous coronary intervention and a planned duration of dual antiplatelet treatment of at least 6 months. Screened patients will be randomly assigned (1:1) using an internet-based randomization with a computer-generated blocking with stratification across study sites to either ticagrelor or clopidogrel treatment. The co-primary primary endpoints are LV remodeling index with three-dimensional echocardiography and the level of N-terminal prohormone B-type natriuretic peptide (NT-proBNP) at 6 months representing post-MI remodeling processes. Changes of LV end-systolic/diastolic volume indices and LV ejection fraction between baseline and 6-month follow-up will be also evaluated. Analysis is per protocol. CONCLUSIONS: HEALING-AMI is testing the effect of ticagrelor in reducing adverse LV remodeling following STEMI. Our trial would show the benefit of ticagrelor vs. clopidogrel related to the recovery of post-MI LV dysfunction beyond potent platelet inhibition. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02224534